Climate change, extreme events and mental health in the Pacific region - Walter Leal Filho; Murukesan Krishnapillai; Aprajita Minhas; Sannia Ali; Gabriela Nagle Alverio; Medhat Sayed Hendy Ahmed; Roselyn Naidu; Ravinesh R. Prasad; Navjot Bhullar; Ayyoob Sharifi; Gustavo J. Nagy; Marina Kovaleva (International Journal of Climate Change Strategies and Management, 2023)
Purpose – This paper aims to address a gap in investigating specific impacts of climate change on mental health in the Pacific region, a region prone to extreme events. This paper reports on a study on the connections between climate change, public health, extreme weather and climate events (EWEs), livelihoods and mental health, focusing on the Pacific region Islands countries. Design/methodology/approach – This paper deploys two main methods. The first is a bibliometric analysis to understand the state of the literature. For example, the input data for term co-occurrence analysis using VOSviewer is bibliometric data of publications downloaded from Scopus. The second method describes case studies, which outline some of the EWEs the region has faced, which have also impacted mental health. Findings – The results suggest that the increased frequency of EWEs in the region contributes to a greater incidence of mental health problems. These, in turn, are associated with a relatively low level of resilience and greater vulnerability. The findings illustrate the need for improvements in the public health systems of Pacific nations so that they are in a better position to cope with the pressures posed by a changing environment. Originality/value – This paper contributes to the current literature by identifying the links between climate change, extreme events, environmental health and mental health consequences in the Pacific Region. It calls for greater awareness of the subject matter of mental health among public health professionals so that they may be better able to recognise the symptoms and relate them to their climate-related causes and co-determinant factors.